2008
DOI: 10.1021/bc800113v
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific, Thiol-Mediated Conjugation of Fluorescent Probes to Cysteine-Modified Diabodies Targeting CD20 or HER2

Abstract: Small, engineered antibody fragments such as diabodies (50 kDa non-covalent dimers of single-chain Fv fragments) are useful alternatives to their larger antibody counterparts. However, due to their size, they are more susceptible to disruption of their antigen binding sites when modified using random conjugation techniques. Previous work has demonstrated the utility of a C-terminal cysteine modification for site-specific radiolabeling of an anti-CEA diabody, resulting in the creation of a cys-diabody (CysDb). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 34 publications
(57 reference statements)
1
44
0
Order By: Relevance
“…There have been a number of other diabodies and minibodies developed for different targets that have been modified for use in bioluminescence (436) and fluorescence (390) imaging studies (see Refs. 113, 317 and TABLE 2 for some examples).…”
Section: Diabodies and Minibodiesmentioning
confidence: 99%
“…There have been a number of other diabodies and minibodies developed for different targets that have been modified for use in bioluminescence (436) and fluorescence (390) imaging studies (see Refs. 113, 317 and TABLE 2 for some examples).…”
Section: Diabodies and Minibodiesmentioning
confidence: 99%
“…DOTA conjugation to antibody fragments was performed according to established protocols (8) by using metalfree buffers. The diabody was reduced by using dithiothreitol and reacted with 1,4,7,10-tetraazacyclododecane-1,4,7-tris-acetic acid-10-maleimidoethylacetamide (Maleimido-monoamide-DOTA; Macrocyclics, Dallas, Tex) as described previously (9).…”
Section: Dota Conjugation and Radiolabelingmentioning
confidence: 99%
“…Hence, the location and number of cysteines (1 per scFv subunit, 2 per diabody) bypasses the issues associated with randomly located, stoichiometrically variable conjugation techniques. The Cys-Db format was recently extended to two additional targets, CD20 (B-cell lymphomas) and Her2/neu (Sirk et al, 2008). In vitro characterization of these fragments showed that the C-terminal cysteines could be readily modified, demonstrating the versatility and reproducibility of the system.…”
Section: Introductionmentioning
confidence: 99%